Respuesta :

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

[tex]4z + 2 = 10z - 1[/tex]

Add sides 1

[tex]4z + 2 + 1 = 10z - 1 + 1[/tex]

[tex]4z + 3 = 10z[/tex]

Subtract sides 4z

[tex] - 4z + 4z + 3 = - 4z + 10z[/tex]

[tex]3 = 6z[/tex]

[tex]6z = 3[/tex]

Divide sides by 6

[tex] \frac{6z}{6} = \frac{3}{6} \\ [/tex]

[tex]z = \frac{1}{2} \\ [/tex]

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

[tex]3y = y + 3[/tex]

Subtract sides y

[tex] - y + 3y = - y + y + 3[/tex]

[tex]2y = 3[/tex]

Divide sides by 2

[tex] \frac{2y}{2} = \frac{3}{2} \\ [/tex]

[tex]y = \frac{3}{2} \\ [/tex]

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

Thus the correct answer is :

[tex]a) \: y = \frac{3}{2} \: , \: z = \frac{1}{2} \\ [/tex]

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️